Inhibition of Rac1 in ventral hippocampal excitatory neurons improves social recognition memory and synaptic plasticity - Zhang, Haiwang; Ben Zablah, Youssif; Zhang, Haorui; Liu, An; Gugustea, Radu; Lee, Dongju; Luo, Xiao; Meng, Yanghong; Li, Song; Zhou, Changxi; Xin, Tao; Jia, Zhengping (Frontiers in Aging Neuroscience, 2022)
Rac1 is critically involved in the regulation of the actin cytoskeleton, neuronal structure, synaptic plasticity and memory. Rac1 overactivation is reported in human patients and animal models of Alzheimer’s disease (AD ) and contributes to their spatial memory deficits, but whether Rac1 dysregulation is also important in other forms of memory deficits is unknown. In addition, the cell types and synaptic mechanisms involved remain unclear. In this study, we used local injections of AAV virus containing a dominant-negative (DN) Rac1 under the control of CaMKIIα promoter and found that the reduction of Rac1 hyperactivity in ventral hippocampal excitatory neurons improves social recognition memory in APP/PS1 mice. Expression of DN Rac1 also improves long-term potentiation, a key synaptic mechanism for memory formation. Our results suggest that overactivation of Rac1 in hippocampal excitatory neurons contributes to social memory deficits in APP/PS1 mice and that manipulating Rac1 activity may provide a potential therapeutic strategy to treat social deficits in AD.